Analysis of the Implementation Life Cycle Assessment (LCA) Method for Identification of Environmental Assessment in Liquid Waste Production Tofu at PT. XYZ - Farida Pulansari; Isna Nugraha (Nusantara Science and Technology Proceedings, 2022)
XYZ is a company engaged in the food industry. The resulting product is tofu. The process of making tofu produces liquid waste from the tofu industry which is disposed of without being treated properly and can cause environmental pollution. The purpose of this research is to help reduce and solve the problems faced by the tofu industry in terms of tofu waste management using the LCA method. In the LCA method, the data will be processed using OpenLCA software. Based on the results of the study, the results of the LCA method were BOD values of 957 mg/l and COD of 1.437 mg/l. This value can pollute the aquatic environment around the tofu production area of PT. XYZ.